Analisis pengatahuan gizi dan produk minunan sari buah kemasan dihubungkan dengan merek yang dikonsumsi pada mahasiswa IPB - Fathiyah Fathiyah; Ujang Sumarwan; Ikeu Tanziha (Media Gizi dan Keluarga, 2005)
The purpose of this study was to analyze the nutrition knowledge and fruit juice beverages product knowledge correlate to consumed brand specifically. The data were collected from 200 IPB students with food and non-food educational background Mann-Whitney test, Friedman test and regression test were used to analyze the data. The result of this study showed that most of the study participants (81,0%) have a good nutrition knowledge, and most of them have a medium level of product knowledge. In liquid form, Buavita brand is the most fruit juice consumed by the study participants, while in powder form is Nutrisari Brand Spearman correlation test showed that there was no significant correlation (p>0,05) between nutrition and product knowledge with fruit juice beverage brand consumed either in powder or in liquidform.